Phage adsorption to Lactobacillus plantarum: influence of physiological and environmental factors. - Briggiler Marcó, Mariángeles (2010)
Bacteriophage infection of lactic acid bacteria (LAB) constitutes one of the major problems in the dairy industry, causing economic losses and a constant risk of low quality and/or unsafe foods. The first step in the phage biology is the adsorption on the host cell surface. In a previous study, a remarkable thermal, chemical and photocatalytic resistance was demonstrated by four phages of Lactobacillus plantarum (ATCC 8014-B1, ATCC 8014-B2, FAGK1 and FAGK2). In the present work, these phages were used to characterize the adsorption process on L. plantarum ATCC 8014. Clearly, the characterization of this process could increase the possibilities of design useful strategies in order to prevent phage infections. The influence of Ca(2+), temperature, pH and physiological cell state on phage adsorption was investigated. Burst sizes of phages ATCC 8014-B1 and ATCC 8014-B2 were 60 and 83 PFU/infective centre, respectively. The four phages exhibited a high infectivity even at pH 4 and pH 11. Calcium or magnesium ions were not indispensable for cell lysis and plaque formation, and more than 99% of phage particles were adsorbed either in the presence or absence of Ca(2+), after 15 min at 37 degrees C. Phage adsorption was only partially affected at 50 degrees C, while reached its maximum between 30 and 42 degrees C. The highest adsorption values (99.9%) were observed from pH 5 to 7, after 30 min at 37 degrees C. Adsorption rates decreased after the thermal inactivation of cells, though, when 20 microg/ml of chloramphenicol was used, adsorption values were similar on treated and untreated cells. All these results showed that the adsorption process was only partially affected by a few conditions: thermally killed host cells, an incubation temperature of 50 degrees C and pH values of 9 and 10. Nevertheless, and unfortunately, those conditions are not commonly applied during fermented food manufacturing, thus restricting highly the application of strategies currently available to reduce phage infections in industrial environments. This work also contributes to increase the currently knowledge on the biological aspects of L. plantarum bacteriophages.